2013
DOI: 10.1007/s00340-013-5454-x
|View full text |Cite
|
Sign up to set email alerts
|

A dual-pass Mach–Zehnder interferometer filter using a TCF loop mirror for double-wavelength fiber lasers

Abstract: A dual-pass Mach-Zehnder interferometer filter using a section of twin-core fiber (TCF) loop mirror is proposed. The filter is theoretically and experimentally studied for various interferometer arm difference when TCF length is constant. Theoretical results are validated by the experimental demonstration and in good agreement with the experimental results. And then, by using the filter in a ring fiber laser, a stable and switchable dual-wavelength lasing is obtained experimentally. The 3-dB bandwidth and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…effect have shown the potential of achieving a multiwavelength comb filter spectrum [6,14,[17][18][19]. The Sagnac loop filter is attractive due to its simple design with fewer passive optical components, low insertion loss, polarization independence and high performance for filter effects [20,21].…”
Section: Large Dynamic Range Operation Of Ultra-higher Number Mwfls A...mentioning
confidence: 99%
“…effect have shown the potential of achieving a multiwavelength comb filter spectrum [6,14,[17][18][19]. The Sagnac loop filter is attractive due to its simple design with fewer passive optical components, low insertion loss, polarization independence and high performance for filter effects [20,21].…”
Section: Large Dynamic Range Operation Of Ultra-higher Number Mwfls A...mentioning
confidence: 99%
“…Stable and tunable narrow-linewidth erbium-doped fibre laser based on polarization-maintaining fibre ring filter and PM-FBG Wei He 1,2 , Lianqing Zhu 1,2 , Mingli Dong 2 , Fei Luo 2 and Xiaohuai Chen 1 2013, Zou et al [7] reported a dual-wavelength erbiumdoped fibre laser (EDFL) based on a dual-pass MZI using a twin-core fibre; when a single line was emitted, the wavelength shift and power fluctuation were 0.02 nm and 0.06 dB respectively, while for dual-wavelength emission, a 0.35 dB peak power drift and a 0.16 nm wavelength interval were obtained. In 2013, Zhou and Luo [8] introduced a tunable EDFL based on an MZI incorporating thermally expanded core fibre; the tuning scope was larger than 40 nm, the wavelength interval was 2.3 nm, and the 3 dB linewidth was smaller than 0.1 nm.…”
Section: Laser Physicsmentioning
confidence: 99%
“…The tuning range for the proposed TDFL was from 1813.52–1858.70 nm. Zou et al reported a multiwavelength EDFL based on a dual‐pass Mach–Zehnder interferomet er (MZI) filter using a twin‐core fiber loop mirror. Using this EDFL, tunable single‐ and dual‐wavelength lines were realized.…”
Section: Introductionmentioning
confidence: 99%